Cryptic hammerhead shark lineage occurrence in the western South Atlantic revealed by DNA analysis - Pinhal, D. [UNESP]; Shivji, M. S.; Vallinoto, M.; Chapman, D. D.; Gadig, Otto Bismarck Fazzano [UNESP]; Martins, C. [UNESP] (Springer, 2012)
A cryptic lineage of hammerhead shark closely related to but evolutionarily distinct from the scalloped hammerhead (Sphyrna lewini) was recently documented in the western North Atlantic Ocean. Here, we demonstrate using nuclear and mitochondrial DNA sequences that this cryptic lineage also occurs in the western South Atlantic Ocean, extending its distribution > 7,000 km from its only previously reported location. Our results also further validate the existence of this evolutionarily distinct hammerhead shark lineage. The southern hemisphere cryptic individuals were 1.6 and 5.8% divergent from S. lewini (sensu stricto) for the nuclear internal transcribed spacer 2 (ITS2) and mitochondrial control region loci, respectively, and formed a strongly supported, reciprocally monophyletic sister group to sympatric S. lewini. Coalescent analysis (ITS2 locus) yielded a divergence estimate of similar to 4.5 million years between S. lewini and the cryptic lineage. Given expanding concerns about overfishing of the large-bodied hammerhead sharks, this cryptic lineage needs to be formally recognized and incorporated into shark management and conservation planning to avoid the inadvertent, potential extirpation of a unique hammerhead lineage.